2020
DOI: 10.3390/ijms21207465
|View full text |Cite
|
Sign up to set email alerts
|

Coelenterazine-Dependent Luciferases as a Powerful Analytical Tool for Research and Biomedical Applications

Abstract: : The functioning of bioluminescent systems in most of the known marine organisms is based on the oxidation reaction of the same substrate—coelenterazine (CTZ), catalyzed by luciferase. Despite the diversity in structures and the functioning mechanisms, these enzymes can be united into a common group called CTZ-dependent luciferases. Among these, there are two sharply different types of the system organization—Ca2+-regulated photoproteins and luciferases themselves that function in accordance with the classica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 254 publications
(277 reference statements)
0
28
0
5
Order By: Relevance
“…This reaction proceeds by two-steps: DLH2 is first adenylated with ATP, and then it is oxidized by O2, to generate excited oxyluciferin, which produces yellow-green light (λmax = 560 nm) [4][5][6][7]. In contrast, bioluminescence in the luminous shrimp, one of many bioluminescent marine species, is generated by the oxidation of coelenterazine (CTZ) catalyzed by oplophorus luciferase (Oluc) in the presence of O2 to generate coelenteramide, which produces blue light (λmax = 454 nm) [8][9][10]. [1], [2], [3], [4], [5], [6], [ Gaussia luciferase (Gluc) Gaussia princeps O2 [1], [2], [3], [8], [9], [10] Renilla luciferase (Rluc)…”
Section: Introductionmentioning
confidence: 99%
“…This reaction proceeds by two-steps: DLH2 is first adenylated with ATP, and then it is oxidized by O2, to generate excited oxyluciferin, which produces yellow-green light (λmax = 560 nm) [4][5][6][7]. In contrast, bioluminescence in the luminous shrimp, one of many bioluminescent marine species, is generated by the oxidation of coelenterazine (CTZ) catalyzed by oplophorus luciferase (Oluc) in the presence of O2 to generate coelenteramide, which produces blue light (λmax = 454 nm) [8][9][10]. [1], [2], [3], [4], [5], [6], [ Gaussia luciferase (Gluc) Gaussia princeps O2 [1], [2], [3], [8], [9], [10] Renilla luciferase (Rluc)…”
Section: Introductionmentioning
confidence: 99%
“…In this review, a summary is presented of the reported molecular design of substrates emitting NIR-I bioluminescence and probes with a focus on the firefly/click beetle luciferin-luciferase system. Similar studies have been carried out in a bioluminescent system using coelenterazine as a substrate, but refer to other excellent reviews [10,11]. There is also a bioluminescent system with bacterial luciferinluciferase reaction, but it is not discussed in this review because it does not require the addition of luciferin from outside; therefore, there is no research on the molecular design of bacterial luciferin [12,13].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, in contrast to luciferases, the CaRP light emission reaction does not require molecular oxygen and CaRP reacts only once, i.e., the one does not “turn over” as an enzyme does . Their broad analytical potential originating from their ability to emit light on Ca 2+ addition causes broad interest in these photoproteins. …”
Section: Introductionmentioning
confidence: 99%